2021
DOI: 10.48550/arxiv.2111.06678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TESS Timings of 31 Hot Jupiters with Ephemeris Uncertainties

Abstract: A precise transit ephemeris serves as the premise for follow-up exoplanet observations. The transit timing variation (TTV) as an important scientific output potentially reveals planetary orbital evolution. We compare transit timings of 262 hot Jupiters from TESS with the archival ephemeris and find 31 of them having significant TESS timing offsets, among which WASP-161b shows the most significant offset of -203.7±4.1 minutes. The median value of these offsets is 17.8 minutes, equivalent to 3.4 σ. We evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…After this work was nearly complete, we became aware of two other groups, Kokori et al (2021a) and Shan et al (2021), who have also been performing transit timing en masse. Since these works are not yet published, we refrained from a detailed comparison between our numerical results and theirs, but we can make some general comparisons.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this work was nearly complete, we became aware of two other groups, Kokori et al (2021a) and Shan et al (2021), who have also been performing transit timing en masse. Since these works are not yet published, we refrained from a detailed comparison between our numerical results and theirs, but we can make some general comparisons.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This team did not utilize TESS data in their study. Shan et al (2021) identified 31 hot Jupiters for which an ephemeris taken from the literature failed to predict the TESS transit times to within the statistical uncertainty. This is different from our approach, which was based on analyzing all available transit times whenever possible, rather than relying on a previously reported ephemeris.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The observed TTV signal and its interpretation are highly dependent on the data quality of timing observation. Any unexpected factors in deriving the transit timing parameters may change the period derivative (detailed example in Yang & Chary, 2021, submitted;Shan et al, 2021), and thus leads to different explanations. Therefore, longbaseline transit monitoring with high precision is crucial for enhancing understanding of the tidal dissipation process.…”
Section: Discussionmentioning
confidence: 99%
“…XO-3b is an another hot Jupiter with significant TTVs (Shan et al, 2021;Yang & Wei, 2021). The planetstar system has an orbit period (P orb ) of 3.19 days, an a of 4.95±0.18, an inclination of 84.20±0.54, and an e of 0.27587 +0.00071 −0.00067 (Winn et al, 2008;Bonomo et al, 2017;Stassun et al, 2017).…”
Section: Sitian Data For Transit Timing Analysis and Simulated Transi...mentioning
confidence: 99%
See 1 more Smart Citation